Analyzing Literature Discourse of Being Unpredictable Aspect of the War Based on the Sociogram - Rabieifar, Mohamad; Ghaemmaghami, Anahita Sadat (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
This article attempts to study the topic of war based on literary studies. For this purpose, this article examines the lecture of Claude Duchet about the sociogram of war. In this study, the unpredictable aspect of war, which means that we cannot imagine and understand the war, is studied. In all societies you can find special thoughts and statements about war, but we always keep in mind incomplete parts of the war that do not encompass the integrity of the war. So we need to look at this in other respects. Although, war is not a literary subject, but literature has to deal with it, ever since war is a human subject. Literature cannot escape war, whether it speaks about it or not.